Phosphorylation‐dependent control of an RNA granule‐localized protein that fine‐tunes defence gene expression at a post‐transcriptional level. (26th November 2019) - Tabassum, Naheed; Eschen‐Lippold, Lennart; Athmer, Benedikt; Baruah, Manaswita; Brode, Martina; Maldonado‐Bonilla, Luis D.; Hoehenwarter, Wolfgang; Hause, Gerd; Scheel, Dierk; Lee, Justin
Summary: Mitogen‐activated protein kinase (MAPK) cascades are key signalling modules of plant defence responses to pathogen‐associated molecular patterns [PAMPs; e.g. the bacterial peptide flagellin (flg22)]. Tandem zinc finger protein 9 (TZF9) is a RNA‐binding protein that is phosphorylated by two PAMP‐responsive MAPKs, MPK3 and MPK6. We mapped the major phosphosites in TZF9 and showed their importance for controlling in vitro RNA‐binding activity, in vivo flg22‐induced rapid disappearance of TZF9‐labelled processing body‐like structures and TZF9 protein turnover. Microarray analysis showed a strong discordance between transcriptome (total mRNA) and translatome (polysome‐associated mRNA) in the tzf9 mutant, with more mRNAs associated with ribosomes in the absence of TZF9. This suggests that TZF9 may sequester and inhibit the translation of subsets of mRNAs. Fittingly, TZF9 physically interacts with poly(A)‐binding protein 2 (PAB2), a hallmark constituent of stress granules – sites for stress‐induced translational stalling/arrest. TZF9 even promotes the assembly of stress granules in the absence of stress. Hence, MAPKs may control defence gene expression post‐transcriptionally through release from translation arrest within TZF9–PAB2‐containing RNA granules or by perturbing the function of PAB2 in translation control (e.g. in the mRNA closed‐loop model of translation). Significance Statement: The zinc finger protein TZF9 determines defence gene expression through translational arrest of mRNAs, with its localization in RNA granules, protein stability and RNA‐binding properties controlled by mitogen‐activated protein kinase‐mediated phosphorylation.